Tracking notch filter for electrocardiograph measurement - Witthayapradit, S.; Chitwong, S.; Tumthong, S. (My University, 2006)
This paper presents a tracking notch filter with opened-loop architecture for elimination of electric field frequency which can also interfere into ECG waveform. For measuring ECG waveform having the isolated instrumentation amplifier, at here, the quality factor (Q) of this filter is assigned about 8 and the attenuation of frequency noise is around of-35 dB and the gain of amplifier is of 1000. The frequency from frequency noise detector is multiplied by the frequency synthesizer. The clock signal from the frequency synthesizer is used for the switched capacitor network The performance of the proposed filter is tested with ECG waveform included frequency noise of 50Hz , 55Hz and 60Hz and also with measuring in Lead I of bipolar lead included noise signal of 50Hz for both cases, that is, before and after through the notch filter circuit in the time and frequency domain. The measured results have been successfully tested. In this paper, the discrete and passive devices are used for the designed circuit.
Keywords: ECG; Line filter; Tracking notch filter